Odontaster validus Koehler 1905 - Jangoux, Michel (Zenodo, 2022)
tenuis Koehler, 1905, Odontaster Odontaster tenuis Koehler, 1905: 468; 1906: 8, pl. 4, figs 33-38. Odontaster validus ‒ Clark 1993: 198. CURRENT STATUS. — Odontaster validus Koehler, 1905. TYPE MATERIAL. — Antarctic • 1 syntype; Howgard Island; French Antarctic expedition; 1903-1905; MNHN-IE-2014-203 • 4 syntypes; same as for preceding; MNHN-IE-2014-335 • 1 syntype; unspecified locality; same as for preceding; MNHN-IE-2014-211 • 5 syntypes; same as for preceding; MNHN-IE-2014-236 • 1 syntype; same as for preceding; MNHN-IE-2014-445. REMARK Koehler (1906) mentions nine specimens:five were collected in Howgard Island waters, the origin of the others is unspecified. Published as part of Jangoux, Michel, 2022, The type specimens of extant asteroids (Echinodermata) in the Muséum national d'Histoire naturelle of Paris, pp. 259-334 in Zoosystema 44 (11) on page 320, DOI:10.5252/zoosystema2022v44a11, http://zenodo.org/record/6616817